Robotic Excision of the Vagina in a 46 XX DSD Male Patient. First Pediatric Report - Torino, Giovanni; Adorisio, Ottavio; Cobellis, Giovanni; Mariscoli , Francesca; Zaccara , Antonio (Urology Journal, 2021)
The Disorders of Sex Differentiation (DSD) represent a wide range of congenital anomalies of the genitalia. Surgical treatment of these cases may become a challenge. We present a case of a 16-year-old boy with 46 XX DSD, SRY negative, presented with persistent dribbling incontinence, recurrent UTI and perineal pain. Past medical history included right orchiectomy, laparoscopic excision of uterus, fallopian tubes and left streak gonad at another institution at the age of 2 years. The native vagina was left in place. VCUG confirmed the presence of the residual vagina (8 cm in maximum length), connected with the bulbar urethra. Robotic-assisted laparoscopy of the vagina was performed with satisfying short and long-term results.